Regional Original Income Management Optimization in Improving Village Economic Development in Rambah Hilir District, Rokan Hulu Regency - Hasan, Amir; Gusnardi, Gusnardi (Proceedings of the UR International Conference on Educational Sciences, 2018)
The purpose of this study is to analyze the optimization of local revenue management in improving the economy in the village. Based on the research objectives, this research is a type of Mixed Methods research. According to Creswell (2007) research using mixed methods is a research approach by combining qualitative and quantitative research. Data collection methods in this study were conducted with interviews, documentation and questionnaires. The data collected is qualitative data and numbers. Data analysis techniques are the process of simplifying data in a form that is easier to read and implement. Data analysis using multiple regression analysis method with hypothesis testing and descriptive analysis. The form of multiple regression equations is formulated in a regression equation about the management of regional original income abbreviated as PAD village to increase the village economy. The results of the study revealed that the management of village PAD carried out by the Village Government was in accordance with its management procedures. Increased rural economic development due to optimal management of the Village PAD, so that the welfare of the people in the village can increase.In general, the management of PAD Desa is in accordance with management in general, starting from planning, organizing, monitoring and accountability. Based on interviews conducted, the Village Government has always set a strategy to coordinate with all actors, especially managers and the Village Government and BPD. With good coordination and cooperation on the management of the Village PAD, the aim of improving the village economy can be done well.